2022
DOI: 10.1007/s11356-022-20071-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Macroeconomic lockdown effects of COVID-19 on small business in China: empirical insights from SEM technique

Abstract: The coronavirus (COVID-19) outbreak in the China has exposed small-and medium-sized enterprises (SMEs) to a variety of challenges, some of which are potentially life-threatening to their sustainability. Therefore, this study aims to investigate the macroeconomic lockdown effects of COVID-19 on small business in China. A survey questionnaire with 313 participants was used to collect the data. In this study, the SEM technique was used to analyse model. The data have been gathered for the study from the managers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 109 publications
0
12
0
Order By: Relevance
“…Rent equipment or tax reductions and loans rose 1.9 percent and 1.1 percent, respectively, indicating that they are the most effective equipment to boost business alive. Many previous studies have demonstrated that the pandemic has had an obvious repercussion on businesses survival (Xiao and Su, 2020;Carracedo and Puertas, 2021;Grondys and Lusarczyk, 2021). Thus, it was expected that the higher the number of lockdown waves, the lower would have been their survival rate.…”
Section: Diagnostic Analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rent equipment or tax reductions and loans rose 1.9 percent and 1.1 percent, respectively, indicating that they are the most effective equipment to boost business alive. Many previous studies have demonstrated that the pandemic has had an obvious repercussion on businesses survival (Xiao and Su, 2020;Carracedo and Puertas, 2021;Grondys and Lusarczyk, 2021). Thus, it was expected that the higher the number of lockdown waves, the lower would have been their survival rate.…”
Section: Diagnostic Analysis Resultsmentioning
confidence: 99%
“…Exposure on online social media could increase product sales during a pandemic and thus improve businesses' survival (Katare and Marshall, 2021). Furthermore, employees' reduction and rent subsidies could reduce the cost of running businesses and increase the probability of their survival (Xiao and Su, 2020).…”
Section: Diagnostic Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many companies had to shut down or limit operations as a result of the pandemic so that the virus would not spread further. SMEs were particularly hard hit since they lacked the financial resources and resiliency of their bigger counterparts [12]. Supply chains were thrown off by lockdowns, travel restrictions, and labor shortages, making it impossible for SMEs to get supplies and components.…”
Section: Impact Of Covid-19mentioning
confidence: 99%
“…This shift not only helped SMEs weather the storm, but also set them up for success in the emerging digital economy. SMEs have trouble keeping a consistent staff due to lockdowns and mobility restrictions [12]. In order to keep businesses running, many people have had to start using remote workers and digital communication technologies.…”
Section: Impact Of Covid-19mentioning
confidence: 99%